Motivation to Learn Arabic for non-Islamic Boarding School Student at Department of Arabic Language Education Antasari State Islamic University Banjarmasin - Rafiatun Najah Qomariah; Norhajizah (Naatiq: Journal of Arabic Education, 2025)
Learning motivation is the internal or external drive that encourages individuals to engage in learning activities. In the context of Arabic language education, motivation plays a crucial role for students without a pesantren (Islamic boarding school) background, as they lack formal Islamic educational exposure compared to their peers who graduated from pesantren. This study aims to identify the factors that influence the learning motivation of fifth-semester students from the 2021 cohort in the Arabic Language Education Department at Antasari State Islamic University Banjarmasin who are not pesantren alumni. The research employed a qualitative descriptive method. Data collection techniques included in-depth interviews, participant observation, and documentation. The informants consisted of purposively selected fifth-semester students who had no pesantren background. Data analysis followed the Miles and Huberman model, consisting of three steps: (1) data reduction, (2) data display, and (3) conclusion drawing/verification. The results reveal that students’ motivation to learn Arabic is influenced by various factors such as personal aspirations, individual abilities, family support, peer influence, and academic environment. These internal and external factors interact to shape the students’ motivational strength in learning Arabic. This study recommends that future research explore the impact of instructional approaches used by lecturers and conduct comparative studies between pesantren and non-pesantren students to deepen the understanding of motivational dynamics in Arabic language learning within Islamic higher education institutions.